Narrativas em abismos: a mise en abyme e a paródia em A audácia dessa mulher, de Ana Maria Machado - Leite, Luana Santana (2025)
This dissertation on The Audacity of This Woman (1999), by Ana Maria Machado, aims to present the work based on theoretical resources from Mise en abyme (Dällenbach, 1975, 1989), which places one text within another, based on narratives that fit together and duplicate themselves through the phenomenon of specularity in literature by constructing three different narratives in the novel, but which complement each other, in relation to the characters not only of her book, but also of Dom Casmurro (1899). To this end, I take as my theoretical basis “The Mirror in the Text” (1989) by Lucien Dallenbach, in which the author develops theories of specularity based on literature, but I seek to expand them from a sociocritical perspective (Labeille, 2011). Furthermore, I will address Metafiction, a phenomenon of fictional self-reference in which a work reflects or duplicates itself, provoking a self-awareness of its fictional character. This is presented in the work based on some of the metafictional resources that are widely used, specifically, narrative metalanguage, intertextuality, promoted by the book's self-reflective narrator/writer, and parody (Hutcheon, 1985), in an intertextual provocation of Machado de Assis's book, which will be discussed through the insertion, mainly, of the construction of a series script, in addition to a diary attributed to the character Capitu in Ana Machado's novel, both intertextual narratives in relation to Dom Casmurro. To construct the analysis, I intend to identify the metalanguage of the narrative creation, connected to Capitu's diary writing based on the narrative webs provoked. To revisit and discuss female characters and female authorship in Brazilian literature, I will start from the research of Branco and Brandão, through A mulher escrita (1989), which analyzed the construction of female characters under male and female authorship, and some names in Feminist Criticism, such as Showalter (1944). The typology of the narrator will also be discussed, based on Friedman (1968) to observe the way in which the narrator presents himself in both books, the choices made in the presentation of the narrative and what are the effects of meaning produced during the reading. With this, we intend to discuss the way in which A audacity of this woman takes possession of literary elements evidenced in the novel in a metalinguistic way.